Analysis of the Validity of Canva Animated Video Media in Pancasila Education Learning Elements of Bhinneka Tunggal Ika in Class V of Elementary School - Mira Maulidya Fajar; Reinita Reinita (Journal of Educational Sciences, 2026)
The lack of use of varied learning media and according to the needs of students in Bhinneka Tunggal Ika material causes low interest and understanding of diversity values. This study aims to analyze the validity of Canva-based animation video media in learning Pancasila Education elements of Bhinneka Tunggal Ika in grade V of elementary school. This research is a type of research and development (R&D) with the ADDIE model which consists of: (1)  analysis, (2) design, (3) development, (4) implementation and (5) evaluation. The data collection instrument is in the form of a validation questionnaire given to media experts, material experts, and linguists. The results of the validity analysis showed that Canva's animated video media was in the very valid category, with a validation score of 89% from media experts, 96% from subject matter experts, and 98% from linguists, resulting in an overall average of 94.3%. Based on these findings, the media developed was declared valid to be used to support the learning of Pancasila Education in the Bhinneka Tunggal Ika element in grade V of elementary school.